(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article is devoted to the actual problem of the formation of youth’s speech culture, in particular students’, since the younger generation defines the vectors for the further development of any society. The connection between students’ speech culture and their learning of subject “Professional Ukrainian language” is grounded. This course includes not only forming of professionally oriented skills of mastery of the Ukrainian literary language in professional sphere, but acculturating, advancing of speech mastery, forming of oral and written fluency in literary form of Ukrainian language in different communicative situations. The author stresses that one of the main tasks of this course is forming of speech culture that is the marker of person’s general knowledge, peculiarities of his / her intelligence, social status. Examples of tasks proposed for students during studying the course. The tasks are selected taking the linguistic situation in Ukraine into account (Ukrainian-Russian bilingualism is meant). The task of forming the language culture of students is solved by a specially selected complex of tasks and exercises, provided for both classroom and independent work. The article suggests some examples of tasks, the implementation of which helps students to master modern linguistic norms, improve their linguistic preparation, and, consequently, the level of speech culture. All proposed tasks are tested. A number of exercises are related to the comparison of certain grammatical structures in the Russian and Ukrainian languages. Students are offered the exercises for grammatical analysis, translating of structures with prepositions, selecting of a normative variant, editing of sentences with logical distortion, explaining of the meanings of paronyms, putting words into the context, selecting Ukrainian equivalents to borrowed words.